Adat Teka Ra Ne’e dalam Kajian Hukum Islam di Desa Tanah Putih Kecamatan Sape Kabupaten Bima - Nadirah Nadirah; Atun Wardatun; Muhammad Mutawali (Fakultas Syariah IAIN Laa Roiba Bogor, 2024)
The Teka Ra Ne’e tradition is a custom carried out by the community when going to school carry out the marriage process. The aim of the Teka Ra Ne'e tradition is to lighten burden on the owner. The aim of this research is to find out the Teka Ra Ne'e traditional procession in the Tanah Putih Village community and to identify how the law views it Islam towards the Teka Ra Ne'e custom in traditional marriages in the Tanah Putih Village community Sape District, Bima Regency. The research method used is research qualitative with a descriptive approach, the collection used is observation, interviews, and documentation. The research subjects were community leaders, traditional leaders and the government Village. Data analysis using interactive models. The results of this research can be concluded that implementation of Teka Ra Ne'e in the Bima traditional wedding procession, especially in Tanah Putih Village Sape District, Bima Regency, namely: (1) Deliberation between families and community leaders, (2) Kaboro haju ka'a, (3) Ti'a haju ka'a, (4) Ndua invitation (dividing invitations), (5) Choosing Ina pangaha, (6) Ndawi Pangaha, (7) Ka eli swamp mbojo, (8) Teka Ra Ne'e, (9) Rice Shedding. Teka Ra Ne'e does not conflict with Islamic law, because it has more benefits rather than the disadvantages such as teaching cooperation (mutual cooperation), friendship, relationship close ties of brotherhood, as well as lightening the burden between people who have a celebration